Machining time and number of machine for the production planning of wheel nut releaser with the demand of 100 units/day - Nanang Qosim; Mohammad Hartono (Institute of Advanced Engineering and Science, 2019)
The impact of competition in the industry has driven people to improve the effectiveness of production process. One of the main factors supporting that effectiveness is the good planning of both the need and the number of machines. The aim of this study is to estimate the machining times to determine the number of machines to manufacture 100/day of the nut releaser tool for car wheel. The result shows that the need of the number of machines to manufacture each component of the nut releaser tool for car wheel are 7 units of power hacksaw, 27 units of lathe machine, 8 units of drilling machine, 12 units of milling machine, 2 units of EDM machine and 25 units of bench work.